Penerapan Algoritma K-Means Clustering Dalam Pengelompokkan Kepadatan Penduduk: Application of K-Means Clustering Algorithm in Population Density Grouping - Delia, Fenita; Rasmita Ngemba, Hajra; Hendra, Syaiful; Syahrullah, Syahrullah; Trezandy Lapatta, Nouval (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2025)
Uneven population density will have a negative impact if not considered. One way to tackle this problem is with population equity management planning policies. This research focuses on clustering population density areas, which is the ratio between population and area in Central Sulawesi Province. This research clustering is applied with data mining techniques, namely K-Means Clustering. The research stages are data collection, data understanding, data processing, clustering, clustering review, dashboard analysis, and accuracy testing with the tableau application in providing visualization of population density in the region. Based on the results of the algorithm calculation, it produces three clusters, cluster 0 being low population density, cluster 1 being high population density, and cluster 2 being medium population density. Cluster formation is based on the visualization produced by the research dataset through Sum Of Square Error analysis, silhouette coefficient, and elbow method. Clustering is formed, followed by dashboard visualization with the tableau application. The clustering results, based on the SSE calculation, produce a value of 4324505738.747303, meaning the determination of the number of clusters with a significant difference with the calculation of the number of previous groupings. Then the results of the silhouette analysis provide the highest average silhouette value at the number of clusters, namely 3 with a value of 0.6144435666457168, and the elbow method gives the result that the elbow point is at point 3, meaning the optimum number of clusters with 3 clusters.